2014
DOI: 10.1039/c3ra44541k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of a laser microstructured fluorine doped tin oxide anode layer with a plasma pretreatment for 3D battery systems

Abstract: Fluorine-doped tin oxide (FTO) films with a thickness of about 3 micrometers were prepared by electron cyclotron resonance-metal organic chemical vapor deposition (ECR-MOCVD) under 800 W of microwave power, with tetra-methyl tin (TMT) as a tin precursor. The dome-shaped micro-patterned FTO layer was prepared on a copper current collector using a KrF excimer laser micromachining system for application as an anode for 3D lithium-ion batteries. Mild ECR plasma treatment at 600 W was carried out on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…3,[8][9][10][11][12] A rather new technical approach is laser structuring of the active material itself for realisation of 3D architectures which has been realised for thin lm electrodes made of LiCoO 2 , LiMn 2 O 4 , SnO 2 or uorine doped SnO 2 . 4,[13][14][15][16][17][18][19][20][21] For each type of electrode material a signicant improvement of specic capacity and cycle retention at high charging/discharging has been achieved due to laser patterning and laser annealing.…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10][11][12] A rather new technical approach is laser structuring of the active material itself for realisation of 3D architectures which has been realised for thin lm electrodes made of LiCoO 2 , LiMn 2 O 4 , SnO 2 or uorine doped SnO 2 . 4,[13][14][15][16][17][18][19][20][21] For each type of electrode material a signicant improvement of specic capacity and cycle retention at high charging/discharging has been achieved due to laser patterning and laser annealing.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the lattice constants of the thin film are, a = 0.4746 Å, c = 0.3194 Å, and the c/a to be 0.6730. It means that FTO deposited on the SUS316 has high corrosion resistance and excellent contact with the SUS316 surface because FTO is deposited on the SUS316 surface form high density film as the polycrystalline structures with the lattice constants of a = 0.4746 Å, c = 0.3194 Å [14,15]. Fig.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…Unfortunately, this approach is unfeasible for each type of electrode system, in particular for thick film electrodes [9][10][11][12][13]. Therefore, laser direct structuring of the active electrode material has been developed for thin film electrodes made of LiCoO 2 , LiMn 2 O 4 , SnO 2 or fluorine doped SnO 2 (FTO) [14][15][16][17][18][19][20][21][22][23]. In a very recent approach, it was shown that laser-structuring can be applied for LiCoO 2 , LiMn 2 O 4 , LiNi 1/3 Mn 1/3 Co 1/3 O 2 and silicon composite electrodes with film thicknesses of 50 to 100 µm [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%